2007
DOI: 10.1007/s11626-007-9060-2
|View full text |Cite
|
Sign up to set email alerts
|

Species identification in cell culture: a two-pronged molecular approach

Abstract: Species identification of cell lines and detection of cross-contamination are crucial for scientific research accuracy and reproducibility. Whereas short tandem repeat profiling offers a solution for a limited number of species, primarily human and mouse, the standard method for species identification of cell lines is enzyme polymorphism. Isoezymology, however, has its own drawbacks; it is cumbersome and the data interpretation is often difficult. Furthermore, the detection sensitivity for cross-contamination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
126
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(132 citation statements)
references
References 33 publications
1
126
0
5
Order By: Relevance
“…First, primers flanking COI were used to amplify the entire gene, and then the 658-bp "barcoding" region was amplified using vertebratespecific primers. 50,51 Host DNA was identified by sequencing the COI gene and using the "Identify Specimen" feature of the Barcode of Life Data Systems (BOLD; www.boldsystems.org).…”
Section: Methodsmentioning
confidence: 99%
“…First, primers flanking COI were used to amplify the entire gene, and then the 658-bp "barcoding" region was amplified using vertebratespecific primers. 50,51 Host DNA was identified by sequencing the COI gene and using the "Identify Specimen" feature of the Barcode of Life Data Systems (BOLD; www.boldsystems.org).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, DNA barcoding has gained wide application in forensic analysis to investigate cases of illegal poaching (Eaton et al 2009), separation of species (Wilson-Wilde et al 2010), gut content analysis in ecological studies (Smith et al 2005;Berry et al 2007;Clare et al 2009), food product analysis and market substitution (Wong and Hanner 2008;Cohen et al 2009), and Asian medicine trade regulation (Peppin et al 2008). DNA barcoding has also been employed to validate the identity of biomaterial collections and cell lines (Lorenz et al 2005;Cooper et al 2007). A sufficient accumulation of DNA barcodes can also help conservation managers to identify interim priority areas for conservation efforts in the absence of species data.…”
mentioning
confidence: 99%
“…Hebert et al (2003) have demonstrated the utility of COI gene as a universal barcode, referred as "DNA barcoding" for the genetic identification of animal life. Recently, Cooper et al (2007) used COI region for identification of 67 cell lines used for barcode analysis. Our analysis also proves the utility of COI gene in the identification of the cell lines from P. denisonii.…”
Section: Resultsmentioning
confidence: 99%